Investment outlook for the medium range tankers (MRs) segment from 2019 – 2023 - Nie, Antong (2019)
This paper is fundamentally based on the discoveries of Volume 1 and Volume 2 to further investigate whether the Medium Range Tanker (MRs) is worth investing in.